(untitled) (Journal of Parents and Teachers, 2023)
Philosophy is usually linked to higher educational levels and sometimes its usefulness in the school curriculum is even debated. In my Final Degree Project, I present an innovative proposal that demonstrates the importance of bringing philosophy to the classroom, even from an early age. This discipline cultivates deep reflection skills, essential in a society in constant change. This work seeks to measure the impact of applying this methodology in a rural classroom.